Optimizing the Role of Applied Maritime Science Education on Logistics Transformation Based on the Automatic Identification System (AIS) in Islamic Countries - Setiawati, Rini; Syukur, Abdul; Wijaya, Hendra (STAI Miftahul Ula Nganjuk, 2023)
This study underscores the pivotal role of applied maritime education in driving the transformation of logistics through the Automatic Identification System (AIS) in Islamic countries. By integrating AIS technology, which enables real-time vessel tracking and monitoring, this research employs a multifaceted approach encompassing literature review, surveys, data analysis, and case studies to assess the current state of maritime education and AIS implementation. The findings emphasize the significance of specialized AIS curricula within maritime education programs and the importance of modern training facilities for fostering practical expertise in AIS technology and logistics management. Collaborative efforts among Islamic countries in curriculum development and facility investments are identified as essential to enhance maritime education's role in AIS transformation. This regional cooperation can facilitate knowledge sharing, best practices, and research, ultimately elevating maritime education standards and global competitiveness while nurturing a more skilled maritime workforce. In conclusion, regional cooperation and investment in modern training facilities are key to unlocking the potential of maritime education, promoting safer and more efficient maritime operations, and driving economic growth and security in Islamic countries.